Protocol for the Reconstructing Consciousness and Cognition (ReCCognition) Study - Maier, Kaitlyn L.; McKinstry-Wu, Andrew R.; Palanca, Ben Julian A.; Tarnal, Vijay; Blain-Moraes, Stefanie; Basner, Mathias; Avidan, Michael S.; Mashour, George A.; Kelz, Max B. (Frontiers in Human Neuroscience, 2017)
Important scientific and clinical questions persist about general anesthesia despite the ubiquitous clinical use of anesthetic drugs in humans since their discovery. For example, it is not known how the brain reconstitutes consciousness and cognition after the profound functional perturbation of the anesthetized state, nor has a specific pattern of functional recovery been characterized. To date, there has been a lack of detailed investigation into rates of recovery and the potential orderly return of attention, sensorimotor function, memory, reasoning and logic, abstract thinking, and processing speed. Moreover, whether such neurobehavioral functions display an invariant sequence of return across individuals is similarly unknown. To address these questions, we designed a study of healthy volunteers undergoing general anesthesia with electroencephalography and serial testing of cognitive functions (NCT01911195). The aims of this study are to characterize the temporal patterns of neurobehavioral recovery over the first several hours following termination of a deep inhaled isoflurane general anesthetic and to identify common patterns of cognitive function recovery. Additionally, we will conduct spectral analysis and reconstruct functional networks from electroencephalographic data to identify any neural correlates (e.g., connectivity patterns, graph-theoretical variables) of cognitive recovery after the perturbation of general anesthesia. To accomplish these objectives, we will enroll a total of sixty consenting adults aged 20-40 across the three participating sites. Half of the study subjects will receive general anesthesia slowly titrated to loss of consciousness with an intravenous infusion of propofol and thereafter be maintained for three hours with 1.3 age adjusted minimum alveolar concentration of isoflurane, while the other half of subjects serves as awake controls to gauge effects of repeated neurobehavioral testing, spontaneous fatigue, and endogenous rest-activity patterns. □